Evaluation of the relationship between periodontal bone loss and Schneiderian membrane thickness in upper posterior teeth with root tips associated with the maxillary sinus: a retrospective cone beam computed tomography study - Kevser Sökmen; Nurullah Sökmen (BMC Oral Health)
Abstract Background This study aimed to examine the effects of periodontal bone loss (PBL) in upper posterior teeth with root tips in contact with the maxillary sinus on sinus mucosal thickening (SMT) via cone beam computed tomography (CBCT). Methods One hundred sixty CBCT images were divided into four equal groups according to the season in which they were taken: spring, summer, autumn, and winter (n = 40). The relationships among sex, age, PBL, and SMT were evaluated. SMT was measured at the site with the greatest distance from the sinus base to the upper edge of the sinus mucosa. SMT exceeding 2 mm was considered pathological. The SMT value was categorized into four classes (Class I: <2 mm, Class II: 2.1–5 mm, Class III: 5.1–10 mm, and Class IV: >10 mm). The PBL level was determined by measuring the distance between the point located 2 mm apical to the cemento-enamel level and the upper border point of the alveolar bone. PBL was calculated by dividing this value by the distance between the apex of the longest root and the point located 2 mm apical to the cemento-enamel border and multiplying by 100. PBL was categorized into three classes (Type I: 25%, Type II: 25–50%, Type III: >50% bone loss). Results No statistically significant relationships were found among sex, season during which the image was taken, the side of the maxillary sinus (right or left) and SMT (p > 0.05). The percentage of Class IV SMT in individuals over 50 years of age (41.9%) was statistically significantly greater than that in other age groups (p < 0.05). The percentage of Class IV SMT in individuals with severe PBL (60.7%) was significantly greater than that in individuals with mild (0%) and moderate (3.2%) PBL (p < 0.05). Conclusions Age and PBL were significantly associated with SMT. As the periodontitis grade (PBL/age) increases, SMT gradually increases.